Influencers perceived usefulness, perceived ease of use and organizational support for the use of e-performance applications using technology acceptance models in regional work units Brebes Regency - Ardian Sulistiyo (Universitas Wiralodra, 2023)
Information and communication technology development has given birth to a public service model carried out through electronic government (e-government). E-government offers public services that can be accessed 24 hours, anytime, and from wherever the user is. One form of E-Government development, namely, the performance appraisal of a State Civil Apparatus (ASN), can become more apparent, measurable, and monitored through the E-Performance application. This study aims to determine the effect of perceived usefulness and ease of use on e-performance applications using the technology acceptance model in the Regional Work Unit (SKPD) of Brebes Regency. This study uses quantitative research methods with linear regression data analysis techniques. Based on the results and discussions that have been done, perceived usefulness, perceived ease of use, and organizational support have an influence and are related to the attitude of using e-performance in the Brebes Regency. With this research, ASN employees can increase the use of the E- Performance application so that the performance that has been carried out can be recorded correctly in the employee's daily work report so that the presentation value of the employee's performance can be maximized.